Hemostatic Properties of the Lymph: Relationships with Occlusion and Thrombosis - Lippi, Giuseppe; Favaloro, Emmanuel J.; Cervellin, Gianfranco (Seminars in Thrombosis and Hemostasis, 2012)
Lymphatic thrombosis is a rare occurrence, and although its frequency is likely underestimated, its burden remains substantially lower than that of venous or arterial thrombosis. Current evidence suggests that despite measurable levels of fibrinogen, von Willebrand factor and other coagulation factors in the lymph, fibrin generation is substantially inhibited under physiological conditions, essentially making the lymph a hypocoagulable biological fluid. Although factor VIIa-tissue factor-catalyzed activation of factor X is possible in the lymph, fibrin generation is largely counteracted by the unavailability of cell surface anionic phospholipids such as those physiologically present on blood platelets, combined with only low levels of coagulation factors, and the strong inhibitory activity of heparin, antithrombin, and tissue factor pathway inhibitor. Enhanced fibrinolytic activity further contributes to reduce the development and growth of lymph clots. Nevertheless, lymphatic thrombosis is occasionally detected, especially in the thoracic duct, axillary, or inguinal lymphatics. Pathogenetic mechanisms are supported by the release of thromboplastin substances from the injured lymphatic endothelium accompanied by chronic obstruction of lymph flow in the presence of a hypercoagulable milieu, thereby mirroring the Virchow triad that otherwise characterizes venous thrombosis. In theory, any source of lymphatic vessel occlusion, such as internal obliteration, external compression, or increased lymphatic pressure, might predispose to localized lymphatic thrombosis. The leading pathologies that can trigger thrombosis in the lymphatic vessels include cancer (due to external compression, neoplastic obliteration of the lymphatic lumen by metastatic cells, or lymphatic dysfunction after lymph node dissection), infections (especially lymphatic filariasis or sustained by Chlamydia trachomatis, Mycobacterium tuberculosis, Treponema pallidum, or Streptococcus pyogenes), congestive heart failure, chronic edema and inflammation of the distal lower limb, complications of central venous catheterization, coronary artery bypass grafting, thoracic outlet syndrome, and amyloidosis.
Keywords: lymphatic thrombosis; vessel; lymph; coagulation